Modelling Analysis of Propylene Glycol as a Cooling Media for Battery Thermal Management System in Electric Vehicles - Shahroom A.F.; A. Rahman N.; Mansor M.; Abd. Rahman M.S. (Springer Nature, 2025)
Ethylene glycol (EG) is an effective coolant for liquid cooling systems in electric vehicles (EVs) but poses significant human and environmental toxicity risks compared to propylene glycol (PG), thus raising safety concerns. However, the use of PG alone has never been done in evaluating its cooling performance for the battery pack of EVs. Hence, this study investigates the cooling efficiency of PG in reducing the battery pack temperatures in EVs, an area that is not previously explored. Using SIMSCAPE library in MATLAB and battery data from literature, the study examines PG at different concentrations under the FTP 752474 drive cycle. The simulation involves two stages: First, running the model with EG at 30, 50, and 60% concentrations and repeating it again using PG. The cooling performance of PG is analysed by comparing the minimum and maximum temperature, and the time taken for the battery pack to reach its minimum temperature. The results indicate that PG is a viable alternative to EG, with temperature differences between these media is only 0.6C for minimum temperature and 0.02C for maximum temperature at 30% concentration. Additionally, PG at 30% concentration provides more stable thermal behaviour for the battery pack compared to EG at the same concentration. On top of that, the concentration of both EG and PG highly affects the cooling performance of the liquid cooling system. This study provides a valuable starting point for future experiments involving PG in EVs. ? King Fahd University of Petroleum & Minerals 2024.